Determination of mass attenuation coefficients, effective atomic numbers and effective electron numbers for heavy-weight and normal-weight concretes - Un, Adem; Demir, Faruk (Pergamon-Elsevier Science Ltd, 2013)
Total mass attenuation coefficients, effective atomic numbers and effective electron numbers values for different 16 heavy-weight and normal-weight concretes are calculated in the energy range from 1 keV to 100 GeV. The values of mass attenuation coefficients used in calculations are taken from the WinXCom computer program. The obtained results for heavy-weight concretes are compared with the results for normal-weight concretes. The results of heavy-weight concretes fairly differ from results for normalweight concretes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Attenuation coefficients; Effective atomic numbers; Effective electron numbers; Heavy-weight concrete